Iron Man 2 - Favreau, Jon.; Theroux, Justin; Debney, John.; Downey, Robert, Jr., 1965-; Cheadle, Don.; Johansson, Scarlett, 1984-; Rourke, Mickey; Jackson, Samuel L.; Paltrow, Gwyneth, 1972-; Rockwell, Sam.; Marvel Entertainment Group; Paramount Pictures Corporation (1914-1927); et al. (Hollywood, CA : Paramount Home Entertainment, 2010)
Now that the world knows billionaire inventor Tony Stark is the armored super hero Iron Man, his life has suddenly become even more intense. Everyone wants in on the Iron Man technology, whether for power or profit, but for Ivan Vanko, it's revenge. With Pepper Potts and James 'Rhodey' Rhodes at his side, Stark must once again suit up and face his most dangerous enemy yet.
Disc 1. Blu-ray feature film + special features -- Disc 2. Blu-ray special features -- Disc 3. DVD feature film + Digital copy.
Special features include: Director commentary; The making of "Iron Man 2"; S.H.I.E.L.D. data vault featurette; Behind-the-scenes featurettes; deleted scenes; concept art gallery; theatrical trailers; AC/DC video "Shoot to thrill."
Editors, Richard Pearson, Dan Lebental ; director of photography, Matthew Libatique ; music by John Debney.
Robert Downey, Jr., Don Cheadle, Scarlett Johansson, Mickey Rourke, Samuel L. Jackson, Gwyneth Paltrow, Sam Rockwell.
Rating: PG-13; for sequences of intense sci-fi action and violence, and some language.
Blu-ray, 1080p High Definition, 5.1 DTS-HD Master Audio, 5.1 Dolby Digital; requires Blu-ray player.
DVD, widescreen presentation, Dolby Digital 5.1 surround.
Keywords: Iron Man (Fictitious character) -- Drama; Superheroes -- Drama; Revenge -- Drama; French language materials; Portuguese language materials; Spanish language materials; Feature films; Action and adventure films; Science fiction films; Superhero films; Video recordings for the hearing impaired